Pengaruh Independensi Auditor terhadap Opini Audit pada Perusahaan Terdaftar di BEI - Judijanto, Loso (Jurnal Akuntansi Dan Keuangan West Science, 2025)
This study examines the effect of auditor independence on the issuance of audit opinions in companies listed on the Indonesia Stock Exchange (IDX). Using a quantitative approach with a sample of 38 auditors, data was collected through a Likert scale survey (1-5) and analyzed using SPSS version 25. The study investigates the relationship between auditor independence and audit opinions, focusing on the likelihood of issuing unqualified, qualified, adverse, and disclaimer opinions. The findings indicate a significant positive relationship between auditor independence and the issuance of unqualified opinions. Furthermore, a negative correlation was found between auditor independence and qualified opinions. The results highlight the importance of maintaining auditor independence to ensure unbiased and reliable audit opinions. This study contributes to the literature by providing insights into the dynamics of auditor independence and its impact on audit quality in the Indonesian context.